2014
DOI: 10.3382/ps.2013-03624
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals an activation of major histocompatibility complex 1 and 2 pathways in chicken trachea immunized with infectious laryngotracheitis virus vaccine

Abstract: Infectious laryngotracheitis is an acute, contagious, upper respiratory disease of chickens caused by gallid herpes virus 1. Due to mortality rates that can reach up to 70% depending on the virulence of the virus, the disease is of great economic importance to the poultry industry. In this study, 15-d-old specific pathogen-free White Leghorn chickens were used to perform transcriptome analysis of chicken trachea immunized with infectious laryngotracheitis virus vaccine. Myosin and several collagen-related gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Although not at the same upregulation level, clustered transcription patterns were observed for IL-2 and IFN-γ genes from 5 dpi to 9 dpi in the mucosal epithelium of the trachea. Luo et al (2014) found that in trachea tissues at late stage of ILTV infection (6 dpi), the transcription of genes related to T cell selection, as well as CD4+ and CD8+, was enhanced. In mammals, IL-2 is secreted by recently activated T cells to enhance their proliferation and facilitate their differentiation to memory T cells, also autocrine production of IL-2 facilitates the differentiation of CD8+ cells to cytotoxic T lymphocytes (CTLs) (Feau et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although not at the same upregulation level, clustered transcription patterns were observed for IL-2 and IFN-γ genes from 5 dpi to 9 dpi in the mucosal epithelium of the trachea. Luo et al (2014) found that in trachea tissues at late stage of ILTV infection (6 dpi), the transcription of genes related to T cell selection, as well as CD4+ and CD8+, was enhanced. In mammals, IL-2 is secreted by recently activated T cells to enhance their proliferation and facilitate their differentiation to memory T cells, also autocrine production of IL-2 facilitates the differentiation of CD8+ cells to cytotoxic T lymphocytes (CTLs) (Feau et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…In order to begin the comprehension of the nature of the immune responses elicited by ILTV infection, general and specific host gene transcription patterns have been evaluated. A study revealed that transcription of major histocompatibility complex I and II antigen processing and presentation genes was significantly increased in the trachea of chickens immunized with a live attenuated vaccine (Luo et al, 2014). A second study found that early after challenge with a virulent ILTV strain transcription of the interferon γ (IFNγ) gene increased in the trachea of chickens immunized with a live attenuated vaccine but transcription of the IFNγ gene remained at a basal level in non-immunized but challenged chickens (Vagnozzi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…(NA: BWA did not detect any BAM alignment across the reference provided.) [17,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] analyzing sequencing data derived from PacBio RS II and Illumina MiSeq sequencing technologies. The only difference detected in our assembled locus sequence relative to the Gallus Gallus (v5) is a 5 bp insertion in the intronic region of chIFITM3.…”
Section: Discussionmentioning
confidence: 99%
“…Chickens only have two granzyme genes, granzyme A and K and their specific functions have not yet been studied in depth. Nonetheless, increased expression of granzyme A mRNA has been observed during immune responses to different virus infections of chickens , and in some of these cases, granzyme A expression also correlated in time with indications of CTL responses . For example, in a recent report , the mRNA expression of granzyme A, CD8α and several proinflammatory cytokines was monitored in the airways of infectious bronchitis virus (IBV)‐infected chickens.…”
Section: Discussionmentioning
confidence: 99%